APPLICATION OF DIGITAL TOOLS IN HR ENGINEERING UNDER THE CONDITIONS OF ECONOMY DIGITALIZATION - VEDERNIKOV, Mykhailo; CHERNUSHKINA, Oksana; KROPYVNYTKSYI, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the application of digital tools in HR engineering in the context of economic digitalization. The importance of integrating digital technologies into HR processes is underscored by the growing demands for efficiency and competitiveness in today’s market. Traditional methods are no longer sufficient to address the challenges modern organizations face, highlighting the need for innovative digital solutions such as video tools, chatbots, data analytics, and artificial intelligence. These tools help optimize HR processes, automate routine tasks, and improve decision-making accuracy, ultimately enhancing employee experience and reducing operational costs.The strategic use of digital tools in HR engineering allows organizations to meet market challenges, streamline workflows, and respond flexibly to the dynamic external environment. The digital transformation of HR processes involves transitioning from manual operations to fully automated systems, with digital tools serving as a roadmap for improving key HR functions and processes. At the core of this transformation is the need to balance technological efficiency with risk management, especially concerning data privacy and potential biases in AI-based systems.The integration of digital HR tools also provides organizations with valuable insights through data analytics, allowing them to assess workforce potential, identify trends, and make informed strategic decisions. The use of artificial intelligence in HR engineering opens new possibilities for talent acquisition, performance management, and employee retention, offering predictive capabilities that enhance long-term organizational planning.Digital HR strategies enable companies to maintain a competitive advantage by ensuring their workforce remains aligned with the evolving market conditions. Special attention is needed to manage the risks associated with AI integration, including issues of data security and algorithmic fairness, which must be addressed to safeguard the integrity of HR processes.
Keywords: digital HR tools; HR engineering; digital transformation; AI in HR; workforce optimization